Assessing Digital Business Sustainability in Thai SMEs: A Study Using Rough Set-Delphi Method and Confirmatory Factor Analysis - Visuthiphol, Saranee; Pankham, Sumaman (Journal of Posthumanism, 2025)
Aim: To assess the structural equation model of digital business sustainability in Small and Medium Enterprises (SMEs) in Thailand, evaluating effective business strategies that will lead to long-term resilience in the digital economy. Methods: The research uses the e-Rough Set Delphi technique to gather expert opinions from 20 experts, divided into three groups: government sector representatives (7 experts), university lecturers in entrepreneurship (6 experts), and successful digital entrepreneurs from SMEs (7 experts). This approach allows for a comprehensive understanding of the factors influencing digital business sustainability. Results: Findings confirm that the proposed sustainability model is reliable and well-structured. It identifies key factors that drive the sustainable development of an SME, with digital transformation being crucial for increasing competitiveness and adaptability. Implications: the implications are practical for policymakers and business leaders in developing strategic frameworks to support SME resilience in the rapidly evolving digital environment. Conclusion: This study contributes to existing literature by proposing a new procedure that combines rough set theory and the Delphi method to measure expert consensus. The research significantly advances the development of tailored strategies to support the sustainability of SMEs in the Thai context and provides a model for economies facing digital disruption.